MANAGEMENT OF MURABAHAH FINANCING STRATEGY IN BMT NU SINGGAHAN TUBAN - Muhammad Syauqi; Irham Zaki; Imron Mawardi (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
In every financial institution, the risk of problematic financing is an absolute must to face. Therefore, every financial institution must implement appropriate strategy and risk management in distributing financing to customers to minimize the risk of problematic financing in the future. The focus of this research is: 1). How is strategic management implemented at BMT NU Singgahan in channeling financing to minimize the occurrence of financing problems? This research uses a qualitative method with a descriptive approach and field research type. Data collection techniques use observation, interviews and documentation methods. The data analysis stages used were data reduction, data presentation, and conclusion drawing, as well as data validity using source triangulation techniques. T The conclusion in this research is 1) Project or Product Selection Determining the project or product that will be financed using murabahah financing. This selection must consider potential benefits, risks, and conformity with sharia principles. 2) Financing Structure: Determine the appropriate murabahah financing structure, including buying and selling price, profit margin, term, and payment schedule. It must comply with sharia principles, including the prohibition of riba (interest) and speculative elements. 3) Risk Management Identify and mitigate risks associated with murabahah financing. This includes credit risk, market risk, operational risk, etc. 4) Performance Monitoring Conduct regular monitoring of projects or products funded with murabahah financing. This includes monitoring finances, project progress and use of funds. 5) Sharia Compliance Ensure that all transactions and activities related to murabahah financing comply with sharia principles. This involves rigorous auditing and monitoring to ensure compliance. 6) Product Development: Striving to continue developing murabahah financing products that are in line with market needs and sharia principles. This involves product innovation and marketing strategies. 7) Regulatory Compliance Ensure that all murabahah financing activities comply with applicable regulations in the company or financial institution's operating area. 8) Liquidity Management Efficient liquidity management to ensure the availability of sufficient funds for planned murabahah financing. 9) Evaluation and Adjustment Carry out regular evaluations of the murabahah financing strategy and make adjustments if necessary based on the results of the evaluation.